(untitled) (Bangladesh Journal of Animal Science, 2015)
The Department of Livestock Services has been implementing Breed Up-gradation Through Progeny Test" Project since 2003, for selecting dairy breeding bulls based on their progeny performance. This paper describes the procedures followed for setting up field based progeny testing scheme involving private farmers and reports the data of progeny testing in Bangladesh from 2007 to 2013. Until now more than 5000 farmers, having at least one Friesian crossbred cow, were registered under this program in 22 districts of the country. Five Friesian crossbred candidate bulls were evaluated on their estimated breeding values for 100-day milk yields of 199 first calving daughters during 2007 to 2013. Out of five bulls, two bulls were found promising due to their positive breeding values compared to the others. By 2015, 100 day lactation milk yield data from more than 450 daughters of 6 candidate bulls (used in 2009) of the second batch are expected to be available for evaluation, and about 2452 daughters (heifers) of different ages produced out of 29 candidate bulls are available under field recording in different geographical areas of the country. So, proven dairy bull production through field-based progeny testing program in Bangladesh is underway. Bang. J. Anim. Sci. 2015. 44(2): 106-112